PENGEMBANGAN MEDIA POWERPOINT INTERAKTIF PADA MATERI BILANGAN DESIMAL DAN BILANGAN BULAT KELAS V SDN SENDANGGUWO 02 - Shalsabila, Rizka; Sary, Ryky Mandar; Rahmawati, Intan (STKIP Persada Khatulistiwa Sintang, 2024)
The research aims to develop PowerPoint media for teaching decimal and whole numbers to fifth-grade elementary school students. This study is a development research utilizing the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research was conducted at grade V in SD Negeri Sendangguwo 02 Semarang. Data collection tools included validation sheets and student questionnaires, with the analysis technique employing descriptive statistical analysis. The subjects of the study were fifth-grade students at SD Negeri Sendangguwo 02. The data obtained were qualitative and then converted into quantitative data. The results of the study indicate that the developed media is highly feasible, with validation percentages of 94.4% from media experts, 93% from content experts, 87.5% from practitioners, and 95.8% from student responses.